2017
DOI: 10.3892/ol.2017.5695
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte elevated gene-1 promotes the proliferation and invasion of breast cancer cells by activating the Wnt/β-catenin signaling pathway

Abstract: Abstract. Astrocyte elevated gene-1 (AEG1) was identified to be overexpressed in breast cancer, and to be associated with the development of breast cancer. In the present study, AEG1 was identified as highly expressed in the MCF-7, MDA-MB-231 and SK-BR-3 breast cancer cell lines and was detected in the MCF-10A normal breast epithelial cell line. The present study established an AEG1-knockdown MCF-7 cell line to investigate the expression status of certain cancer-associated proteins. Western blotting demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Overexpression of AEG1 has been documented to be involved in many tumors' biological processes, including tumor proliferation, metastasis, EMT. [12][13][14][15] To evaluate the possibility that AEG1 is important for HCC, we examined AEG1 expression in corresponding noncancerous tissues and HCC using Gene Expression Profiling Interactive Analysis (GEPIA) website based on TCGA database. 16 Notably, AEG1 expression in HCC samples was significantly higher compared to normal samples ( Figure 3A).…”
Section: Aeg1 Is Identified As a Target Of Mir-885-5pmentioning
confidence: 99%
“…Overexpression of AEG1 has been documented to be involved in many tumors' biological processes, including tumor proliferation, metastasis, EMT. [12][13][14][15] To evaluate the possibility that AEG1 is important for HCC, we examined AEG1 expression in corresponding noncancerous tissues and HCC using Gene Expression Profiling Interactive Analysis (GEPIA) website based on TCGA database. 16 Notably, AEG1 expression in HCC samples was significantly higher compared to normal samples ( Figure 3A).…”
Section: Aeg1 Is Identified As a Target Of Mir-885-5pmentioning
confidence: 99%
“…In another study, using TOP‐Flash reporter assay and Western blot was indicated that SOX14 remarkable activated Wnt/β‐catenin signaling. The authors demonstrated that SOX14 can promote proliferation and invasion capacity of CC cell lines (HT‐3, Caski, HeLa, and SiHa) by activating the Wnt/β‐catenin cascade [Li et al, ]. In one study which seeks novel approach for modulating cisplatin sensitivity in CC achieved interesting results.…”
Section: Wnt Pathway As a Prognostic Markermentioning
confidence: 99%
“…Astrocyte-elevated gene-1 (AEG-1) is encoded on chromosome 8q22 [ 14 ], and upregulation of AEG1 was confirmed in various malignant tumors [ 15 , 16 ]. In addition, aberrant AEG1 expression is correlated with a poor clinical prognosis and chemoresistance in patients with tumors [ 17 – 19 ].…”
Section: Introductionmentioning
confidence: 99%